Analisis Kesalahan Siswa SMP pada Materi Perbandingan berdasarkan Perspektif Gender dan Analisis Kesalahan Newman. - Nida Fathiya Hanifah; Wahyu Hidayat; Usman Aripin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This research was conducted to find out how the gender perspective affects the mistakes made by students in the ratio and proportion questions. Mindset’s differences between male and female will affect how they solve problems and it will also affect their mathematics learning outcomes. Errors made by students were analyzed using the Newman error analysis indicator. Error analysis indicators used are reading errors, misunderstanding errors, transformation errors, process errors, and error writing answers (encoding). This research uses descriptive qualitative research method. This research was conducted at SMPN 2 Cimahi. The instruments in this study were test and non-test questions. It can be concluded from this research that there are differences between male and female students when working on ratio and proportion concept questions based on the mistakes they’ve made. The most common mistakes made by male students are mistakes in the process of writing answers. This error occurs because they do not write down the complete answer details, it’s because male tend to be simpler in solving problems. The most common mistake made by female is an error in understanding. It’s because female tend to use logic-less when understanding the mathematical problems presented in the questions.